Allometric scaling of force-velocity test output among pre-pubertal basketball players - Martinho, D. V.; Baptista, R.; Teixeira, A. S.; Duarte, J. P.; Valente-dos-Santos, J.; Coelho-e-Silva, M. J.; Cupido Santos, A. M.; Armstrong, N. (International Journal of Sports Medicine, 2021)
Basketball is characterized by high-intensity episodes predominantly reliant on anaerobic metabolism. The force-velocity test enables individual determination of an optimal braking force and emerged as appropriate to estimate optimal peak power. It has rarely been used in youth basketball. This study aimed to examine the contribution of body size, composition, and biological maturation to interindividual variation in force-velocity test output among pre-pubertal basketball players. The sample consisted of 64 male participants (8.4-12.3 years). Stature, sitting height, body mass and two skinfolds were measured, and leg length estimated. Fat-free mass and lower limb volume were estimated from anthropometry. Age at peak height velocity was predicted from maturity offset. Optimal peak power was correlated with all body size descriptors (correlation: 0.541-0.700). Simple allometric models explained 30-47% of inter-individual variance, with fat-free mass being the best predictor of performance. Whole-body fat-free mass (as a surrogate for active muscle mass) plus the indicator of maturation emerged as the best proportional allometric model (53% explained variance). Even at pre-pubertal ages, the interpretation of the force-velocity test requires assessing the metabolically active component of body mass.